Crystal structure of the human carbonic anhydrase II adduct with 1-(4-sulfamoylphenyl-ethyl)-2, 4, 6-triphenylpyridinium perchlorate, a membrane-impermeant, isoform selective inhibitor. (1st January 2018) - Alterio, Vincenzo; Esposito, Davide; Monti, Simona Maria; Supuran, Claudiu T.; De Simone, Giuseppina
Abstract: Pyridinium containing sulfonamides have been largely investigated as carbonic anhydrase inhibitors (CAIs), showing interesting selectivity features. Nevertheless, only few structural studies are so far available on adducts that these compounds form with diverse CA isoforms. In this paper, we report the structural characterization of the adduct that a triphenylpyridinium derivative forms with hCA II, showing that the substitution of the pyridinium ring plays a key role in determining the conformation of the inhibitor in the active site and consequently the binding affinity to the enzyme. These findings open new perspectives on the basic structural requirements for designing sulfonamide CAIs with a selective inhibition profile. Graphical Abstract: